PERAN POLISI DALAM UPAYA PENCEGAHAN KASUS PENGGELAPAN KENDARAAN MOBIL OLEH KEPOLISIAN DI WILAYAH HUKUM POLRES BULELENG - Kadek Wahyu Saputra (Jurnal Komunikasi Hukum, 2025)
This study aims to (1) explain the role of the police in preventing cases of vehicle embezzlement in the jurisdiction of the Buleleng Police and, (2) to reveal the process of investigating perpetrators of criminal acts of vehicle embezzlement by the police in the jurisdiction of the Buleleng Police. The type of research used is empirical legal research with a qualitative descriptive research nature. The location of this research was conducted at the Buleleng Police. The data collection techniques used were first documentation, second observation and third interviews. The sampling technique used was Non Probability Sampling with Purposive Sampling. The data processing technique used was qualitative data analysis. The results of the study indicate that (1) the role of the police in preventing cases of vehicle embezzlement by the Buleleng Police is carried out through preventive efforts (prevention) and repressive efforts (action); (2) The process of investigating perpetrators of criminal acts of vehicle embezzlement by the police in the jurisdiction of the Buleleng Police, is carried out through several stages, namely: reports from the public, investigations, investigations, arrests, examinations and exile. From the explanation, there are requirements and stages of the investigation process against perpetrators of criminal acts of embezzlement of motor vehicles.